A Mathematical Theory of Evidence turns 40 - Shafer, Glenn (International journal of approximate reasoning, 2016)
The book that launched the Dempster–Shafer theory of belief functions appeared 40 years ago. This intellectual autobiography looks back on how I came to write the book and how its ideas played out in my later work.